Research on 3D Printed Scaffolds Loaded With Extracellular Vesicles to Regulate the Microenvironment of Periodontitis Microbiota and Promote Tissue Regeneration - Ma, Xun (International Journal of Public Health and Medical Research, 2026)
In recent years, extracellular vesicles have been widely recognized as important mediators of communication between cells, as they contain bioactive molecules and have the potential to regulate immunity and promote regeneration. 3D printed scaffolds can simulate extracellular matrix structures to provide directional spatial guidance for regenerating microenvironments. The purpose of this study is to develop a three-dimensional printed scaffold system with extracellular vesicles and evaluate its intervention in the microenvironment of periodontitis microbiota and promotion of periodontal tissue regeneration; Simultaneously improve the extraction and characterization methods of extracellular vesicles, and screen suitable biomaterials and their 3D printing processes to obtain composite scaffolds with appropriate porosity, mechanical strength, and release characteristics. Evaluate the inhibitory effect of the scaffolds on periodontal pathogens and their ability to regulate bacterial homeostasis at the in vitro level, and observe whether they affect macrophage polarization and the expression of inflammatory factors; Then, by establishing an animal periodontitis model, the repairing effect of the stent on the alveolar bone defect area and the fusion status of the newly formed tissue were observed. The results showed that the composite scaffold can significantly inhibit the number of pathogenic bacteria, rebuild microbial diversity, alleviate inflammatory reactions, and significantly promote the formation of alveolar bone and periodontal ligament like tissues. In summary, this article provides a new approach for the comprehensive treatment of periodontitis: microbial microenvironment regulation combined with tissue engineering technology.